1981
DOI: 10.1128/aac.19.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Activity of Ionophores with Other Antibacterial Agents Against Anaerobes

Abstract: Representative polyethers of each group in Westley's classification and related ionophore antibiotics were examined for in vitro activity against 25 anaerobic strains. Lasalocid (X-537A) and nigericin were found to have activity comparable in potency to some leading antianaerobe antibiotics, newer cephalosporins and nitroimidazoles, with a different spectrum as revealed by a spectral comparison. A strict relationship between their antianaerobe activity and either their structural features or cation transportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The reason for this incomplete cross-resistance remains unclear. Acquired resistance to ionophores has not yet been reported either for clostridia (33,34,72,79,82,129,228) or for other anaerobic bacteria (228).…”
Section: Vol 16 2003 Antimicrobial Growth Promoters In Animals 181mentioning
confidence: 99%
See 3 more Smart Citations
“…The reason for this incomplete cross-resistance remains unclear. Acquired resistance to ionophores has not yet been reported either for clostridia (33,34,72,79,82,129,228) or for other anaerobic bacteria (228).…”
Section: Vol 16 2003 Antimicrobial Growth Promoters In Animals 181mentioning
confidence: 99%
“…It transports Na ϩ more efficiently than K ϩ (48,108). Lasalocid is a divalent ionophore antibiotic (228). Although it transports bivalent ions such as Ca 2ϩ and Mg 2ϩ very well (176), it is also an efficient K ϩ carrier (48).…”
Section: Vol 16 2003 Antimicrobial Growth Promoters In Animals 181mentioning
confidence: 99%
See 2 more Smart Citations
“…and Staphylococcus spp. in the concentration range from 0.25 μg/mL to 16 μg/mL (12). These compounds are usually applied in the form of the corresponding sodium complexes, which possess strong antimicrobial efficacy, but many studies have revealed that their biological activity is sensitive to the local cation(ii) environment both in in vivo and in vitro experiments (1,2,3,4,5).…”
Section: Introductionmentioning
confidence: 99%